STRATEGI PEMBELAJARAN AL-QUR’AN YANG EFEKTIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA - Ulum Rajabul Khasanah; Diah Wahyuningsih (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to identify and analyze effective Qur'an learning strategies in improving students' Qur'an reading skills at Al Ishlah Special Program Elementary Madrasah. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and document analysis. The results of the study indicate that the application of the talaqqi and tahsin methods, as well as the use of interactive digital media, contribute significantly to improving the quality of students' Qur'an reading. The talaqqi method allows direct correction by teachers, while the tahsin method encourages improvement through structured exercises. On the other hand, the use of digital media such as interactive applications and learning videos supports more enjoyable independent learning. Individual and group approaches also strengthen the effectiveness of learning through personal attention and a collaborative learning atmosphere. The implications of this study indicate that learning strategies that integrate traditional methods and modern technology need to be continuously developed by madrasahs and educators to optimize Qur'an learning outcomes sustainably. Keywords: Learning Strategies, Qur’an, Reading Ability, Students, Learning Effectiveness